A new prognostic pelvic injury outcome score - Luigi Meccariello; Cristina Razzano; Cristina De Dominicis; Juan Antonio Herrera-Molpeceres; Francesco Liuzza; Rocco Erasmo; Guido Rocca; Michele Bisaccia; Enzo Pagliarulo; Pietro Cirfeda; David Gómez Garrido; Giuseppe Pica; et al. (Medicinski glasnik, 2020)
Aim: To propose a new prognostic classification system for pelvic injuries based on a new detailed and all-encompassing evaluation of the injury pelvic outcome score and to check the prognostic value of this classification and evaluate its reliability and reproducibility. Methods: From January 2017 to June 2020 from 156 pelvic fractures treated at our hospitals, 98 patients with pelvic fractures were recruited according to inclusion and exclusion criteria. All patients compiled three scores (New Score System, Majeed Score, SF-12) sessions two times during the hospital stay to evaluate the endpoint before the trauma and two years after the trauma. All patients carried out three tests independently. The evaluation of three scores included a pelvic and general complication after the surgery, the times needed to compile three score system. For reliability of the new score systems we evaluated the inter-observer or intraobserver agreement, the prediction strength of each score, and a prognostic value. Results: A total of 98 patients were enrolled (74 were males and 24 females) with mean age of 43.6 (±18.6) (range 16-75) years. Tau B Kendall value was 0.827 for the new score system, 0.673 for the Majeed score, 0.746 for SF-12, there was p<0.05 for the new score system. Conclusion: The new score system is prognostic, reliable, reproducible and can become a useful instrument to adequately correlate the long-term outcomes of pelvic injury fractures. Also, it provides a better evaluation of pain, work, sexual possibilities and satisfaction, balance-sitting-walking and psychological status.
Keywords: dysfunction; outcomes; pain; work